Optimasi Beban AS Truk Untuk Meminimalkan Biaya Transportasi Dan Kerusakan Konstruksi Jalan (Studi Kasus Ruas Jalan Solo-Kartosura-Boyolali Provinsi Jawa Tengah) - Sugiyanto, Gito (Jenderal Soedirman University, 2005)
This research is aimed at defining the optimum axle load of trucks, in a way to produce both minimum transportation cost and damage construction road. Apart from formulating ways to minimize government expenditures in handling road maintenance, this research has investigated a new paradigm as an alternative of road maintenance considering the principles of cost recovery. This means that overloading trucks will have to bear Road User Tax-a tax reflecting their destructive impacts on roads.The result indicate that: Medium good vehicles have an optimum load of 7,500 ton and minimum transport cost of Rp 19.275,54 per vehicle-trip, Heavy good vehicle (HGV) trucks 2 axles 13 ton have an optimum load of 12,667 ton and minimum transport cost of Rp 37.735,21 per vehicle-trip, HGV trucks 3 axles 20 ton have an optimum load of 21,00 ton and minimum transport cost of Rp 52.730,36 per vehicle-trip and HGV trucks 4 axles have an optimum load of 26,50 ton and minimum transport cost of Rp 45.014,25 per vehicle-trip. The average of Road User Tax in effort of the pure cost recovery for: Medium good vehicles have Rp 20,89 per vehicle-trip, HGV trucks 2 axles 13 ton have Rp 195,68 per vehicle-trip, HGV trucks 2 axles 13 ton have Rp 142,96 per vehicle-trip, and HGV trucks 2 axles 13 ton have Rp 489,66 per vehicletrip. A trip in this case is 25,30 km.